2015
DOI: 10.1145/2814847
|View full text |Cite
|
Sign up to set email alerts
|

Computing numerically with functions instead of numbers

Abstract: Science and engineering depend upon computation of functions such as flow fields, charge distributions, and quantum states. Ultimately, such computations require some kind of discretization, but in recent years, it has become possible in many cases to hide the discretizations from the user. We present the Chebfun system for numerical computation with functions, which is based on a key idea: an analogy of floating-point arithmetic for functions rather than numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Since (4.1) is an asymptotic expansion, it can only be used for sufficiently large k. For this paper, j 0,k is tabulated for k ∈ [1,20] and computed by means of (4.1) if k > 20.…”
Section: Lagrange Inversion Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Since (4.1) is an asymptotic expansion, it can only be used for sufficiently large k. For this paper, j 0,k is tabulated for k ∈ [1,20] and computed by means of (4.1) if k > 20.…”
Section: Lagrange Inversion Theoremmentioning
confidence: 99%
“…Because these functions need only be evaluated in the range φ ∈ [0, π 2 ], they are good candidates to be approximated by means of Chebyshev interpolants [19,20]. However, the presence of a singularity at φ = rπ, ∀r ∈ {±1, ±2, ±3, ...} slows down the convergence of the Chebyshev series.…”
Section: 2mentioning
confidence: 99%
“…A comparison of univariate Taylor forms and Chebyshev forms in [27] showed that expansions in Chebyshev series may be orders of magnitude more accurate than expansions in Taylor series. The use of Chebyshev series expansion as an arithmetic is also the philosophy behind the package Chebfun by Trefethen et al [6,57], which has recently been extended to functions in two variables as well [56]. It should be noted that Chebfun relies on computations with functions to 15-digit accuracy, thus removing the need for propagating a remainder term, but the results are not validated per se.…”
Section: Introductionmentioning
confidence: 99%
“…It was implemented in a 2004 paper [3] for the smooth functions on the interval [−1, 1] with the aim of building some links between the discrete and continuous linear algebra in particular to extend the MATLAB operations made on vectors and matrix in the functions and the operators. The basis of Chebfun is Chebyshev polynomials [33,34]. Chebfun computes Chebyshev coefficients by examining them in the machine precision of a function g and represents it to the Chebyshev points by using barycentric interpolation [10].…”
Section: Chebfun Systemmentioning
confidence: 99%